Quest towards the Core of Selfhood - Amjad, Naumana; Misbah, Farah (Islamic Studies, 2014)
This paper traces the progression of a quest for understanding the core of human self. There are three separate but mutually influential descriptions of this quest. First, in section one we describe an academic exploration, a theoretical research on concept of human self across various religious philosophical and spiritual traditions of the world; The Second section provides an overview of empirical research, and final section see elaborate in more detail Islamic Spiritual Tradition of ‘Sufism’ in its doctrine and practice, and a qualitative investigation of spiritual strengths. The theoretical research concludes that parallel concepts about the origin of self are found across the various wisdom traditions. These traditions agree that human self is composed of physical, mental and spiritual levels. Empirical investigations include the development of a scale of spiritual attitude and an experiment that has demonstrated that religious meditation can increase spiritual attitude and happiness and reduce anxiety. Further studies have examined religious gratitude, jealousy, and the connection between spirituality and higher human consciousness.